Speech Acts and Implicature in Media Framing: A Pragmatic Study of Gus Miftah's 'Goblok' Controversy on Detik.com - Saragih, M Afiv Toni Suhendra (English Teaching and Linguistics Journal (ETLiJ), 2025)
This study conducts a pragmatic analysis of how Detik.com's editorial texts framed the prolonged controversy surrounding Gus Miftah's "Goblok" remark to an iced tea seller. Employing a descriptive qualitative methodology with documentation techniques, the research specifically examines three pragmatic elements: (1) speech acts (locutionary, illocutionary, and perlocutionary), (2) conversational implicatures, and (3) presuppositions in media discourse. The findings reveal that Detik.com strategically employed these pragmatic devices to construct particular narrative frames, significantly influencing readers' interpretations of the incident. Notably, the analysis demonstrates how assertive, directive, and expressive speech acts were utilized to shape public perception, while carefully crafted implicatures and presuppositions reinforced specific ideological positions. Furthermore, this study evaluates these media framing strategies through the lens of Islamic communication ethics, highlighting critical tensions between journalistic framing techniques and Islamic values that emphasize fairness (al-'adl), truthfulness (as-sidq), and prudent speech (hifzh al-lisan). The research contributes to both media studies and Islamic communication ethics by providing empirical evidence of how pragmatic devices operate in digital journalism and offering normative reflections on responsible media practices in Muslim contexts. Practical implications suggest the need for media literacy initiatives to help audiences critically engage with framed content.